Application of Attribution Theory to Understand Renewable Energy Users’ Perceptions - Nufian S Febriani; Fitria Avicenna (Universitas Muhammadiyah Yogyakarta, 2022)
Weiner’s attribution theory is used in this study to explain the perceptions and attitudes of early adults in using renewable energy. Energy policy in Indonesia supports the development of the use of renewable energy. However, this policy contradicts the still high use of fossil energy as the biggest support for the national electricity demand. This policy raises various perceptions in society, especially in early adulthood. The method used is quantitative with a survey of 135 respondents. Sampling using simple random to respondents with an age range of 18-40 years. The results of this study indicate that the perceptions and attitudes formed are quite positive. They show a high interest in using renewable energy whose information they get from social media. Researchers found that early adults’ perceptions and attitudes toward information on social media were predictable and explainable. The early adult age group showed a higher internal attribution value than external attribution on the use of renewable energy provided by social media. This shows that the perception and attitude toward using renewable energy are positive and the behavior that may arise from the information it consumes. Thus, the results of this study can be used as recommendations for policymakers to use social media as the main media to gain trust from early adults, especially for the use of renewable energy in Indonesia.